Kesenian Barongan Kabupaten Pati dalam Pergeseran Budaya - Laura Andri Retno M (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Traditional arts are used to express the beauty of the human soul. In traditional artwork implicit message of the society of knowledge, ideas, beliefs and values norms. One example of a traditional art that has the function of rituals is Barongan. Barongan  is a community-owned art Kabupaten Pati, Jawa Tengah raised to preserve the culture and values in society. Through a qualitative descriptive approach with observation techniques and literature, it was found that at the next stage of development, especially in the modern society, arts performances Barongan shift function just as more entertainment. Barongan existence as art and traditional culture in Indonesia progressively eroded by the expansion of global art and culture. Therefore, efforts must be made to preserve the arts and culture in the midst of changing times and foreign cultural influences have been increasing in Indonesia